Impact of including two types of destoned olive cakes in pigs’ diets on fecal bacterial composition and study of the relationship between fecal microbiota, feed efficiency, gut fermentation, and gaseous emissions - Belloumi, Dhekra; García-Rebollar, Paloma; Calvet, Salvador; Francino, M. Pilar; Reyes-Prieto, Mariana; González-Garrido, Jorge; Piquer, Laia; Jiménez-Belenguer, Ana Isabel; Bermejo, Almudena; Cano, Carmen; Cerisuelo, Alba (Frontiers in Microbiology, 2024)
The microbial population in the pig's gastrointestinal tract can be influenced by incorporating fibrous by-products into the diets. This study investigated the impact of including two types of dried olive cake (OC) in pigs' diets on fecal bacterial composition. The correlation between fecal microbiota and growth performance, nutrient digestibility, and slurry gas emissions was also evaluated. Thirty male Pietrain x (Landrace x Large white) pigs (47.9 ± 4.21 kg) were assigned to three groups: a control group (C), a group fed a diet with 20 % partially defatted OC (20PDOC), and a group fed a diet with 20 % cyclone OC (20COC) for 21 days. Fecal samples collected before and after providing the experimental diets were analyzed for the V3-V4 region of the 16S rRNA gene. Pigs were weighed, and feed intake was recorded throughout the study. Potential ammonia and methane emissions from slurry were measured. No significant differences in alpha diversity indexes were found. The taxonomic analysis revealed that Firmicutes and Bacteroidota phyla were dominant at the phylum level across all groups. Differential abundance analysis using ALDEx showed significant differences among groups for various bacteria at the phylum, genus, and species levels at the end of the experiment. Pigs from 20PDOC and 20COC groups exhibited increased abundances of health-promoting bacteria, such as Plactomycetota at the phylum level and Allisonella and an unidentified genus from the Eggerthellaceae family at the genus level. These changes influenced short-chain fatty acids’ (SCFA) concentration in slurries, leading to greater acetic, butyric, caproic and heptanoic acids in OC-fed groups, especially 20COC pigs. A volatility analysis revealed significant positive correlations (p < 0.05) between Uncultured_Bacteroidales and Unculured_Selenomonadaceae and energy digestibility. Monoglobus and Desulfovibrio showed a positive significant (p < 0.05) correlation with total SCFA, indicating a high impact on gut fermentation. However, growth performance parameters and potential gas emission displayed no significant correlations with a specific bacterial genus. In conclusion, our results suggest that OC inclusion into pig diets could positively modulate and contribute to the gut microbiota's favorable composition and functionality. Also, nutrient digestibility and gut fermentation patterns can be associated with specific microbial populations.